Predicting Middle School Profiles of Algebra Performance Using Fraction Knowledge. Issue 5 (30th April 2021) - Barbieri, Christina Areizaga; Young, Laura K.; Newton, Kristie J.; Booth, Julie L.
Abstract : Fraction knowledge and algebraic skill are closely linked. Algebra is a gatekeeper for advanced courses (Booth & Newton, 2012; Brown & Quinn, 2007). This study uses the person‐centered approach of latent profile analysis to examine individual differences in middle schoolers' ( N  = 350) algebra performance at the end of the year (EOY). The relative importance of a range of fraction skills is considered in predicting the likelihood of displaying a particular profile of EOY algebra knowledge, measured by feature knowledge, equation encoding, equation solving, and word‐problem skills. Notably, fraction number line estimation did not predict algebra performance on any of the four measures. Fraction arithmetic at the beginning of the year is most predictive of displaying the highest performing EOY algebra profile.